RECENT GENERALIZED METRIC SPACES AND RELATED FIXED POINT THEOREMS - Hala Nadjet (University Eloued جامعة الوادي, 2024)
In this thesis, some fixed point theorems are studied on different spaces, using a class of functions, new contractionsare introduced on dislocated quasi b-metric spaces and on dislocated b-metric spaces, and the fixed point theorem is presented for a self mapping satisfying a generalized con traction condition. Finally, two applications are presented to prove the ex istence of solutions to: integral equations of the Volterra type and the boundary value problem of fractional differential equations. في هذه الاطروحة، تمت دراسة بعض نظريات النقطة الثابتة على فضاءات مختلفة باستخدام فئة من الدوال، تم تقديم تقلصات جديدة في فضاءات من نوع ب-شبه متريه المترية المفككة، وفضاءات من نوع ب-المترية المفككة، وعرض نظرية النقطة الثابتة لتطبيق ذاتي يلبي شرط تقلصي معمم. اخيرا، قدمنا تطبيقين لاثبات وجود حلول لكل من: معادلة تكاملية من نوع فولتيرا، و مسألة القيمة الحدية للمعادلات التفاضلية الكسيرية
Thèse de Doctorat
Keywords: Dislocated quasi b; metric space; dislocated b-metric spaces; fixed point theorem; الفضاءات من نوع ب; شبه المترية المفككة; المترية المفككة; نظرية النقطة الثابتة